2017
DOI: 10.1038/srep42591
|View full text |Cite
|
Sign up to set email alerts
|

New findings of silica nanoparticles induced ER autophagy in human colon cancer cell

Abstract: Nanoparticle-induced autophagy has been extensively studied, however, real time information about the endoplasmic reticulum involved autophagic process (ER autophagy) induced by nanomaterials remains unknown. In this work, silica nanoparticles (SNPs) were synthesized with characteristics of low toxicity, good biocompatibility and excellent water dispersibility to treat cells. Results show that either low concentration (10 μg/mL) or high concentration (200 μg/mL) of SNPs could increase the quantity of processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
(58 reference statements)
2
26
0
1
Order By: Relevance
“…Moreover, we found that the SiNPs selectively activated ER stress via activating the EIF2AK3 and ATF6 pathways but not the ERN1-XBP1pathway. Our results are partially in line with a recent report, which also showed that SiNPs localized in the ER and induced ER autophagy in human colon cancer cells [19]. Another report showed that SiNPs activated ER stress via HSPA5 upregulation and XBP1 splicing [42], while our results indicated that SiNPs not only enhanced HSPA5 expression but also activated the EIF2AK3 and ATF6 pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, we found that the SiNPs selectively activated ER stress via activating the EIF2AK3 and ATF6 pathways but not the ERN1-XBP1pathway. Our results are partially in line with a recent report, which also showed that SiNPs localized in the ER and induced ER autophagy in human colon cancer cells [19]. Another report showed that SiNPs activated ER stress via HSPA5 upregulation and XBP1 splicing [42], while our results indicated that SiNPs not only enhanced HSPA5 expression but also activated the EIF2AK3 and ATF6 pathways.…”
Section: Discussionsupporting
confidence: 93%
“…SiNPs have been shown to induce autophagy in various cell lines, such as HCT-116 human colon cancer cells, HepG2 human hepatoma cells, HUVECs, and RAW 264.7 murine macrophage cells [3,[19][20][21]. Moreover, our group and others have also reported that SiNPs induce autophagy dysfunction via lysosomal impairment and inhibition of autophagosome degradation [5,22].…”
Section: Introductionmentioning
confidence: 66%
“…It has been reported that silica nanoparticles accumulate in the endoplasmic reticulum and triggers autophagy [67]. On the other hand, the intracellular accumulation of gold nanoparticles leads to inhibition of macropinocytosis and reduction of endoplasmic reticulum stress [68].…”
Section: Effect Of Nanoparticles On the Endoplasmic Reticulum And Golmentioning
confidence: 99%
“…[100,101] Polymeric nanoparticles such as 3-hydroxybutyrate-co-3-hydroxyhexanoate (PHBHHX), [113] polyethylenimine (PEI), [103,104] amino-terminated polyethylene glycol (PEG-NH 2 ), [145] polyethylene glycol (PEG) block copolymers poly(lactic-co-glycolic acid) (PEG-b-PLGA), [105] poly(lacticco-glycolic acid) (PLGA), [106,107] H40-poly(d,l-lactide), [102] polystyrene, [108][109][110]146] polyplexes, [112] and nanogels [111] are taken www.advancedsciencenews.com www.advtherap.com up by cells through the endocytosis pathway or another uptake pathway and degraded through autophagy pathway. [102][103][104][105][106][107][108][109][110][111][112] Metal nanoparticles including alpha-aluminum oxide, [119] copper, [120,121] cobalt chromium-molybdenum, [122] cuprous oxide, [124] iron oxide, [125,126] cobalt and chromium, [123] silica, [127][128][129][130]133] silver, [131,132] zinc oxide, [134,…”
Section: Selective Autophagy Of Nanoparticlesmentioning
confidence: 99%